Role of heart rate variability and regulatory-adaptive status index in predicting the heart transplant rejection - M. Kh. Lepshokova; E. D. Kosmacheva (Российский кардиологический журнал, 2022)
Aim. To assess the diagnostic value of heart rate variability (HRV) parameters and regulatory-adaptive status index and their prognostic value after orthotopic heart transplantation.Material and methods. The study included 70 patients after orthotopic heart transplantation using a modified bicaval technique performed in the period from 2012 to 2015. The follow-up period was 36±1 month. Most of the recipients were men — 59 (84,29%). The mean age was 50,24±10 years. Twelve, 24 and 36 months after the operation, recipients underwent right ventricular endomyocardial biopsy, 24-hou relectrocardiographic monitoring, and a cardiorespiratory synchronization (CRS) test. Statistical data processing was carried out using the Statistica 10 software (StatSoft Inc., version 10.0.228.8, Oklahoma, USA). The informativeness of studied parameters in predicting rejection episode was assessed by ROC analysis.Results. Twelve months after transplantation, rejection episode was diagnosed in 23 (33%) recipients, 24 months — in 23 (34,8%), 36 months — in 19 (29,6%). CRS characteristics did not differ significantly depending on the presence of a rejection episode as 12 months after surgery (p>0,2) and subsequently (p>0,3). HRV values in the first year after surgery did not show differences in the groups with a rejection episode. After 2 years, the high-frequency component of the HRV frequency domain had the highest predictive value (AUC=0,693, p=0,005). Three years after the operation, all analyzed HRV parameters demonstrated informative value for the diagnosis of rejection episode, the highest predictive value among which had the heart rate (AUC=0,873, p<0,001).Conclusion. The study of HRV should be considered to assess the risk of a rejection episodes in recipients 2 and 3 years after surgery. The regulatory-adaptive status index, being an integral value of cardiac transplant reinnervation, does not demonstrate predictive value in relation to the rejection episode within 3 years after transplantation. However, it confirms the fact of cardiac transplant reinnervation and allows assessing the regulatory-adaptive status of recipients after surgery.